Parasite-Driven host manipulation: The case of trematodes in Neotropical tadpoles - Rosa, Paula Maria [UNESP]; de Souza Queiroz, Murilo [UNESP]; Pelinson, Rodolfo Mei; Anjos, Luciano A. [UNESP]; de Cerqueira Rossa-Feres, Denise [UNESP] (Elsevier, 2024)
Parasites can impact tadpole survival in both lethal and sublethal ways. Sublethal effects include alterations in morphology and behavior, reduced competitive ability, and increased vulnerability to predation, while lethal effects result in direct mortality. These impacts can have significant consequences at both individual and population levels, especially given that amphibians host various parasites and pathogens, which may contribute to population declines. This study investigated the influence of digenetic trematodes, specifically Lophosicyadiplostomum sp. and Echinostomatidae metacercariae – larval stages found in second intermediate hosts, on the development and behavior of Physalaemus cuvieri tadpoles. Behavioral experiments assessed tadpole activity (time and movement number), water column use, and food consumption rates using video recordings and image analysis. Swimming performance was evaluated through predation simulations, and tadpole morphology (i.e. body size and mass) was measured post-experimentally. Infections by these digenetic trematodes resulted in a notable reduction in tadpole activity. A negative correlation was observed between Lophosicyadiplostomum sp. parasite load and both tadpole activity duration and movement frequency, indicating a common response to trematode infection. This study underscores the need for further research on digenetic trematodes to determine whether these behavioral modifications represent host manipulation by the parasites, potentially optimizing their transmission to the final host.
Keywords: Anuran tadpoles; Digenetic trematodes; Host manipulation; Trophic transmission